ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN DI DUA ZONA WILAYAH INDONESIA (WIB & WITA) TAHUN 2014-2020 MENGGUNAKAN MODEL EKONOMETRIKA DATA PANEL DINAMIS DENGAN PENDEKATAN GENERALIZED METHOD OF MOMENT ARELLANO-BOND - Dedi Setiawan; Didit Welly Udjiyanto; Akhmad Syari’udin (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Various countries in the world face the same problem, namely poverty. Poverty is a problem that is often discussed in the media and is a source of major problems in every country, especially in Indonesia. The phenomenon of poverty will continue to exist every year and become a major problem for the government to eradicate poverty in Indonesia. The problem of poverty should not be ignored but must be minimized so that the case of poverty in Indonesia can be resolved optimally. Macroeconomic factors on the development of poverty levels in Indonesia in this study will only discuss the causes of poverty in the form of macro characteristics. Macro characteristics that will be used in this study include gross regional domestic product (GRDP), human development index (IPM), open unemployment, inflation rate, and information and communication technology (ICT). This study aims to examine the effect of regional gross domestic product, human development index, open unemployment, inflation rate, and information and communication technology in two zones of Indonesia (WIB & WITA) in 2014-2020 from the results of poverty reduction, so that it can be used as consideration in policy making. This research data was taken from the website of the Central Statistics Agency (BPS) in Indonesia. The dynamic panel data regression analysis method with the Generalized Method of Moment Arellano-Bond approach is carried out using the E-views 10 application. The results of the dynamic panel data regression model chosen are the first difference generalized method of moment (FD-GMM). Based on the results of the analysis, it shows that the GRDP in the western zone (WIB) has a significant effect on the poverty level and the central zone (WITA) has no significant effect on the poverty level. HDI and Open Unemployment in the western zone (WIB) and the central zone (WITA) have the same significant effect on poverty levels. Inflation rates and Information and Communication Technology (ICT) in the western zone (WIB) and the central zone (WITA) have the same not significant effect on poverty levels